2018
DOI: 10.1016/j.rmed.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung abnormalities are associated with increased mortality in smokers

Abstract: Interstitial lung abnormalities were common in this lung cancer screening population of relatively healthy smokers and were associated with mortality regardless of the interstitial morphological phenotype. The increased mortality was partly due to an association with lung cancer and non-pulmonary malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 17 publications
(29 reference statements)
4
45
1
2
Order By: Relevance
“…Lung cancer CT screening studies report ILA prevalence of 4.0–16.7% . A Japanese screening cohort that included 48% never smokers reported a rate of 2.6% .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lung cancer CT screening studies report ILA prevalence of 4.0–16.7% . A Japanese screening cohort that included 48% never smokers reported a rate of 2.6% .…”
Section: Introductionmentioning
confidence: 99%
“…Although the significance of ILA is not clearly defined, studies have found associated decrements in exercise capacity, reduced health and functional status, decline in lung function and increased risk of all-cause mortality and pulmonary fibrosis specific mortality. [4][5][6][7][8][9] Detection of ILA in populations receiving CT scans for other reasons may provide much needed insights into the natural history of fibrotic lung disease and inform the discussion about indications for treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICD10codes used to define the specific diseases and disease groups are listed in Supplementary Table 1. We used Cox regression analysis to handle the censoring that was introduced by the known increased mortality of participants with ILA [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of a higher mortality from lung cancer and pulmonary fibrosis in patients with ILA [7,13]. However, the prevalence of ILA is much higher than the prevalence of ILDs as clinical entities and only a few of all people with ILA develop clinical disease [7,[13][14][15][16]. The role of ILA in the early detection of ILD remains to be established.…”
Section: Introductionmentioning
confidence: 99%